Bisphenol A Mineralization by Integrated Ultrasound-UV-Iron (II) Treatment (2007)
ABSTRACT: Bisphenol A (BPA), an organic compound largely used in the plastic industry as a monomer for production of epoxy resins and polycarbonate, is an emerging contaminant that is released in the environment from bottles and packaging. BPA degradation (118 μmol L-1) under sonochemical conditions was investigated in this study, using a 300 kHz frequency, with a 80 W electrical power. Under these conditions, BPA was eliminated by the ultrasound process (∼90 min). However, even after long ultrasound irradiation periods (10 h), more than 50% of chemical oxygen demand (COD) and 80% of total organic carbon (TOC) remained in the solution, indicating that most BPA intermediates are recalcitrant toward ultrasonic action. Accumulation of hydrogen peroxide from °OH and °OOH radical recombination was also observed. To increase the efficiency of BPA treatment, experiments combined ultrasound with Fe2+ (100 μmol L-1) and/or UV radiation (254 nm):  Ultrasound/UV; Ultrasound/Fe2+; Ultrasound/UV/Fe2+. Both UV and Fe2+ induced hydrogen peroxide dissociation, leading to additional °OH radicals and complete COD and TOC removal. Thus difficulties in obtaining mineralization of micropollutants like BPA through ultrasonic action alone, can be overcome by the Ultrasound/UV/Fe2+ combination. Moreover, this technique was found to be the most cost-effective one. So, the integrated ultrasound-UV-iron(II) process was shown to be of interest for the treatment of wastewaters contaminated with BPA